2018
DOI: 10.17810/2015.78
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Beliefs College English Instructors’ Held About Teaching Reading Strategies and Their Classroom Practice

Abstract: This study examined connections between beliefs college English language instructors' held about reading strategies and how they implemented them in teaching reading. The sites of the target population for this study were the Colleges of Teacher Education students in Amhara National Regional State Council, Ethiopia. In this region, there are 10 Administrative Zones. In the zones, there are 10 colleges. Among these, 4 colleges were selected by simple random sampling technique. From the 4 selected colleges, 26 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Other research has shown quite different results, from studies finding a relationship between beliefs and teaching practices in reading learning (Cunningham and Zibulsky, 2009;Tolchinsky and Ríos, 2009;Rapoport et al, 2016) to studies which indicated a moderate correlation (Baumann et al, 1998). On the opposite side, other authors found no such relationship (Pérez-Peitx, 2013;Miglis et al, 2014;Enyew and Melesse, 2018;Utami et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Other research has shown quite different results, from studies finding a relationship between beliefs and teaching practices in reading learning (Cunningham and Zibulsky, 2009;Tolchinsky and Ríos, 2009;Rapoport et al, 2016) to studies which indicated a moderate correlation (Baumann et al, 1998). On the opposite side, other authors found no such relationship (Pérez-Peitx, 2013;Miglis et al, 2014;Enyew and Melesse, 2018;Utami et al, 2019).…”
Section: Discussionmentioning
confidence: 85%